Management of Fractures Shaft of Tibia in Adult Interlocking Nailing Versus Plating in: A Comparative Study - Islam, Md Ashraful; Rashid, Md Abdur; Islam, Md Rafiqul; Milon, Md Hafizur Rahman; Mahmud, Md Kaiser (KYAMC Journal, 2019)
Background: Tibial shaft fractures are the commonest long bone fractures in adults, most commonly managed by intramedullary interlocking nailing. However, several meta-analysis show that locking plate osteosynthesis is equally effective in managing tibial diaphyseal fractures and are associated with less number of complications. Aim: To compare the results of fixation of tibial fractures followingplating and nailing in terms of union, patient satisfaction and complications. Materials and Methods: Khwaja Yunus Ali Medical College and Hospital based non randomized clinical trial was performed from September 2014 to August 2017 where closed or open diaphyseal or metaphyseo- diaphyseal fractures of the tibia (closed or open Gustilo Anderson type 1 through 3B) were included. Simple sequential allocation was used for allotting the patients to two groups, one for interlocking nailing and other for plating. The patients were followed up for clinical, radiographic and functional results. Results: Forty patients with 41 involved limbs completed followup for one year. in our study was 19.55±0.69 weeks in case of interlocking nailing and 20.38±1.39 weeks in case of plating and there was no statistically significant difference between the two. Conclusion: There was no difference between the twomodalities in terms of fracture union. Complications were lesser but more serious in case of plating. Patient satisfaction was more with plating. KYAMC Journal Vol. 10, No.-2, July 2019, Page 99-105